2013
DOI: 10.1073/pnas.1303090110
|View full text |Cite
|
Sign up to set email alerts
|

UGA is an additional glycine codon in uncultured SR1 bacteria from the human microbiota

Abstract: The composition of the human microbiota is recognized as an important factor in human health and disease. Many of our cohabitating microbes belong to phylum-level divisions for which there are no cultivated representatives and are only represented by small subunit rRNA sequences. For one such taxon (SR1), which includes bacteria with elevated abundance in periodontitis, we provide a single-cell genome sequence from a healthy oral sample. SR1 bacteria use a unique genetic code. In-frame TGA (opal) codons are fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
318
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 283 publications
(329 citation statements)
references
References 37 publications
10
318
0
1
Order By: Relevance
“…13a). The same recoding was found and biochemically validated in candidate phylum SR1 very recently 41 , suggesting that this codon reassignment may be phylogenetically widespread in uncharacterized lineages. This expands the known alternative coding for UGA, which has previously been reported for selenocysteine 42 and tryptophan 43,44 .…”
Section: Functional Diversity and Novel Findingssupporting
confidence: 56%
“…13a). The same recoding was found and biochemically validated in candidate phylum SR1 very recently 41 , suggesting that this codon reassignment may be phylogenetically widespread in uncharacterized lineages. This expands the known alternative coding for UGA, which has previously been reported for selenocysteine 42 and tryptophan 43,44 .…”
Section: Functional Diversity and Novel Findingssupporting
confidence: 56%
“…For example, we demonstrated that single-cell genomes from uncultivated phyla substantially improve the phylogenetic anchoring of metagenomic reads 1 . Mapping of metagenome sequences to single-cell genomes has not only been applied to validating metagenome assembly and binning 7 but also to subsequently improving the single-cell assemblies, as has been shown for SR1 bacteria, atribacteria and ammoniaoxidizing archaea [8][9][10] . Other studies successfully used fragment recruitment by single-cell genomes to investigate biogeographic distribution of uncultivated, marine taxa 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the number of bacterial genomes in a given collection of scaffolds in a raw assembly or in a curated genome bin, and to visualize the distribution of HMM hits for each bacterial single-copy gene, we used the anvi'o script 'gen-stats-for-single-copy-genes', which reports the most frequent number in the list of number of hits per single-copy gene as the estimated number of bacterial genomes in a collection of scaffolds. The script uses HMMer v3.1b2 [39] to search for Hidden Markov Profiles (HMMs) of 139 bacterial single-copy genes identified by Campbell et al [11], and the R library 'ggplot' v1.0.0 [40,41] to plot results.…”
Section: Methodsmentioning
confidence: 99%
“…Although Boothby et al reported the lack of 16S rRNA genes in their assembly [29], anvi'o estimated that it contained at least 10 complete bacterial genomes (Fig. 2) using a bacterial single-copy gene collection [11]. This simple yet powerful step could identify cases of extensive contamination, and alert researchers to be diligent in identifying scaffolds originating from bacterial organisms.…”
Section: Best Practices To Assess Bacterial Contaminationmentioning
confidence: 99%
See 1 more Smart Citation